2004
DOI: 10.1007/s10334-004-0067-3
|View full text |Cite
|
Sign up to set email alerts
|

Vessel size imaging using low intravascular contrast agent concentrations

Abstract: Vessel size index (VSI) measurements have been validated on rats bearing a glioma with high doses of contrast agent. The aim of this study was to evaluate the impact of using a reduced dose of contrast agent, necessary for clinical trials. Experiments were performed on rats at three doses of AMI-227 and clearly show higher VSI values at lower doses, whatever the region of interest (contralateral, peritumoral and intratumoral tissue). These results are in good correlation with Monte-Carlo simulations on healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 12 publications
3
22
0
Order By: Relevance
“…Therefore, in accordance with those model calculations, a GE-EPI BOLD increase across the relevant field range can only be expected for high spatial resolution to emphasize the contribution of very small vessels. However, with our spatial resolution of 400 ϫ 400 ϫ 2000 m 3 , the rather large voxels will have a strong weighting toward vessel diameters Ͼ3 m, in correspondence with vessel size determinations by Troprès et al (2001Troprès et al ( , 2004, who reported diameters of 5 m or more in rat brain based on both their experimental data and Monte Carlo calculations. These spatial conditions therefore support also the lack of BOLD field dependence for GE-EPI of our data.…”
supporting
confidence: 79%
“…Therefore, in accordance with those model calculations, a GE-EPI BOLD increase across the relevant field range can only be expected for high spatial resolution to emphasize the contribution of very small vessels. However, with our spatial resolution of 400 ϫ 400 ϫ 2000 m 3 , the rather large voxels will have a strong weighting toward vessel diameters Ͼ3 m, in correspondence with vessel size determinations by Troprès et al (2001Troprès et al ( , 2004, who reported diameters of 5 m or more in rat brain based on both their experimental data and Monte Carlo calculations. These spatial conditions therefore support also the lack of BOLD field dependence for GE-EPI of our data.…”
supporting
confidence: 79%
“…A quantitative comparison of the calculated vessel size index obtained by VSI and the histologically estimated vessel size has so far been performed on tumor models of the rat 9,19,22,23,25,36 and of the mouse, 21 the latter performing a sound comparison with intravital optical microscopy minimizing artifacts by histological preparation and restricting the evaluation to functionally active capillaries. For human gliomas, a histological investigation of the microvessel area, microvessel density, and microvessel inhomogeneity in correlation with the relative CBV has previously been published, but not for the vessel size itself.…”
Section: Discussionmentioning
confidence: 99%
“…This information is highly relevant for the diagnosis of pathological microvascular changes, for example angiogenesis in tumours (Tropres et al, 2004;Kiselev et al, 2005;Quarles and Schmainda, 2007;Lin et al, 2008;Valable et al, 2008).…”
Section: Introductionmentioning
confidence: 99%